The The Commercial Value of Guangxi Miao Batik in Douyin Short Video Communication - Junrui Ma (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Purpose-This study analyzes the current situation and characteristics of the communication of Guangxi Miao batik on the Chinese social media (Douyin), and explores the commercial value of this Chinese intangible cultural heritage spread on Douyin.Methodology-This research uses a qualitative research method which collects data by interview method and network observation method. To use the theory of symbolic interaction theory to analyze the current situation and characteristics of Guangxi Miao batik communication on Douyin.Results-Miao batik has a lot of content and characters that can be developed and shared in Chinese social media (Douyin). Batik culture communication has achieved certain results under social media by the government, the media, and many individuals. However, there are still many problems, such as the lack of application of new media technology, the need to improve and innovate content quality, and the lack of combination of Miao batik communication and market development. To create representative social media works that spread Guangxi Miao batik, we must be good at using new media technology, while improving the quality of communication content and realizing the combination of batik communication and e-commerce.Practical implications-This study promotes the introduction of batik products to the market as special tourist souvenirs, and integrates them with fashion design, home design, cultural and creative peripherals and other fields. This study puts forward some suggestions to further improve the dissemination of Guangxi Miao batik on Chinese social media (Douyin) and promote the protection and inheritance of batik craftsmanship.